Current Status and Future Perspectives on Minimally Invasive Esophagectomy - Kawakubo, Hirofumi (Korean Society for Thoracic and Cardiovascular Surgery, 2013)
Esophageal cancer has one of the highest malignant potentials of any type of tumor. The 3-field lymph node dissection is the standard procedure in Japan for surgically curable esophageal cancer in the middle or upper thoracic esophagus. Minimally invasive esophagectomy is being increasingly performed in many countries, and several studies report its feasibility and curability; further, the magnifying effect of the thoracoscope is another distinct advantage. However, few studies have reported that minimally invasive esophagectomy is more beneficial than open esophagectomy. A recent meta-analysis revealed that minimally invasive esophagectomy reduces blood loss, respiratory complications, the total morbidity rate, and hospitalization duration. A randomized study reported that the pulmonary infection rate, pain score, intraoperative blood loss, hospitalization duration, and postoperative 6-week quality of life were significantly better with the minimally invasive procedure than with other procedures. In the future, sentinel lymph node mapping might play a significant role by obtaining individualized information to customize the surgical procedure for individual patients' specific needs.